Serological Profile of Anti-Toxoplasma gondii Antibodies in Liver Transplant Recipients - Gabriella Beltrame Pintos; Francielly Camilla Bazílio Laurindo Pires; Nathália Zini; Rita Cássia Martins Alves da Silva; Francisco Inaldo Mendes Silva Junior; Renato Ferreira da Silva; Tainara Souza Pinho; Luiz Carlos de Mattos; Cinara Cássia Brandão (Tropical Medicine and Infectious Disease)
Toxoplasma gondii (T. gondii), a globally distributed obligatory intracellular opportunistic parasite that has infected one third of the world population, has different transmission routes including via organ transplantation. The liver has emerged as a frequent transplanted organ in which the transmission of T. gondii can occur between seropositive donors and seronegative recipients. Allied with immunosuppressive therapy, the presence of latent infection in recipients elevates the risk of severe toxoplasmosis. The goal of this study was to evaluate the demographic, clinical, epidemiological, and anti-T. gondii antibody profiles in liver transplant recipients. All demographic, clinical, epidemiological, and serological data were obtained from the electronic medical records of liver transplant recipients from the Liver Transplantation Service of the Hospital de Base in São José do Rio Preto, Brazil, from 2008 to 2018. Data from 48 eligible recipients (females: n = 17; males: n = 31) were evaluated. The recipients were grouped according to their T. gondii serological profiles (G1: IgM−/IgG−; G2: IgM−/IgG+; G3: IgM+/IgG+; G4: IgM+/IgG−). The overall mean age was 55.3 (±15.3) years; the age difference between women (42.7 ± 17 years) and men (62.2 ± 10.9 years) was statistically significant (p-value > 0.0001). The percentages of the serological profiles were 20 (n = 41.7%), 26 (n = 54.1%), and 2 (n = 4.2%) for G1, G2, and G3, respectively. No recipient had a serological profile for G4. Hepatosplenomegaly (47.9%), fever (35.4%), encephalopathy (20.8%), and headache (16.7%) were commonly observed symptoms. No statistically significant differences were observed between the serological group and clinical data (p-value = 0.953). The percentages of coinfection by T. gondii with hepatitis A, B, and C were 47.9%, 20.8%, and 12.5%, respectively. About 41.7% of the recipients later died. The data demonstrate that infection by T. gondii is common in liver transplant recipients, and it is not associated with the analyzed demographic, clinical, and epidemiological data.